Gd doped molybdenum selenide/carbon nanofibers: an excellent electrocatalyst for monitoring endogenous H2S. Issue 11 (26th April 2021) - Jeromiyas, Nithiya; Lin, Chun-Mao; Yu-Chieh, Lee; Chen, Ching-Hui; Mani, Veerappan; Arumugam, Rameshkumar; Huang, Sheng-Tung
Abstract : Design and synthesis of Gd doped molybdenum selenide/carbon nanofibers for monitoring H2 S. Abstract : In recent years, transition metal dichalcogenides have become increasingly popular in electrochemical sensors due to their excellent redox properties. Herein, a highly efficient electrocatalyst Gd 3+ doped molybdenum selenide with carbon nanofibers (Gd-MoSe2 /CNF) is synthesized for electrocatalytic sensing of H2 S. The synthesis involves a facile and quick hydrothermal treatment. The morphological, elemental, electrochemically active surface area, and impedance properties were investigated to understand its sensing capability. Gd-MoSe2 /CNF showed excellent electrocatalytic ability to oxidize H2 S. The overpotential for oxidation was minimized to +0.10 V, Ag/AgCl, and the response current increased two-fold compared to control electrodes. High sensitivity, acceptable selectivity, robustness and appreciable reproducibility were observed. The linear range was 12.5 nM–1.2 mM and the detection limit was 1 nM. The method was successful in tracking H2 S secreted by HeLa cells. Our reports suggest that Gd-MoSe2 /CNF is a useful material in monitoring endogenous H2 S.